Assessment of public transport demand and supply characteristics for the UP campus - Katipunan route - Carreon, Jacob P.; Florendo, Raphael Louis D.
The main objective of this study is to determine the total passenger demand which includes served and unserved passenger demands of the UP Campus-Katipunan jeepney route which involves two transport lines (Katipunan-UP Campus and Katipunan-Balara); and to calculate the required number of jeepneys and compare it to the actual unit supply for both operating lines. The served passenger demand is obtained by analyzing data obtained from transport surveys namely - Boarding and Alighting Survey and License Plate Survey while the unserved demand is calculated by sensitivity analysis wherein the unserved demand is estimated as a percentage of the total demand. The calculation of the required number of jeepney units is based from the Route Measured Capacity Method. Another goal of this study is also to generate the desire lines of the UP-Katipunan route as obtained from the Origin- Destination Survey. From the findings of this study, it is concluded that both of the transport lines do not have enough units to satisfy the demand for a day. However, this will not be the case if only the number of roundtrips of each jeepney is increased or the number of jeepneys operating per day is increased.